A lineage 1 branch porcine reproductive and respiratory syndrome virus live vaccine candidate provides broad cross-protection against HP-like PRRSV in piglets - Chao Li; Jinhao Li; Bangjun Gong; Hu Xu; Zhenyang Guo; Lirun Xiang; Siyu Zhang; Qi Sun; Jing Zhao; Menglin Zhang; Yan-Dong Tang; Chaoliang Leng; et al. (Virulence)
Multiple porcine reproductive and respiratory syndrome virus (PRRSV) subtypes coinfect numerous pig farms in China, and commercial PRRSV vaccines offer limited cross-protection against heterologous strains. Our previous research confirmed that a PRRSV lineage 1 branch attenuated live vaccine (SD-R) provides cross-protection against HP-PRRSV, NADC30-like PRRSV and NADC34-like PRRSV. HP-PRRSV has undergone significant genetic variation following nearly two decades of evolution and has transformed into a subtype referred to as HP-like PRRSV, which also exhibits high pathogenicity. The effectiveness of immunising piglets with the SD-R strain to provide protection against infection with HP-like PRRSV remains uncertain. In the present study, we evaluated the protective effects of SD-R vaccine strains on DLF-challenged piglets. The results revealed that piglets challenged with DLF presented clinical symptoms such as continuous high fever and an obvious decrease in daily weight gain. Importantly, the piglets immunised with SD-R exhibited notable reductions in pathological damage, especially of decreases in DLF-induced thymic atrophy. Moreover, the serum of SD-R-immunised piglets strongly neutralised DLF, and the number of SD-R-vaccinated piglets demonstrating viraemia was greatly reduced. These results suggest that the PRRSV lineage 1 branch live vaccine candidate provides broad cross-protection against HP-like PRRSV in piglets.